Antimicrobial Activity of Green Synthesized Silver and Copper Oxide Nanoparticles against the Foodborne Pathogen Campylobacter jejuni - Daniel Rivera-Mendoza; Beatriz Quiñones; Alejandro Huerta-Saquero; Ernestina Castro-Longoria (MDPI AG, 2024)
Campylobacter jejuni is a major cause of global foodborne illnesses. To develop alternative antimicrobial strategies against C. jejuni, this study designed and optimized the green synthesis of metallic nanoparticles (NPs) with intracellular components of the medicinal fungus Ganoderma sessile to provide the needed reducing and stabilizing agents. NPs were characterized by transmission electron microscopy and dynamic light scattering, and the quasi-spherical NPs had sizes of 2.9 ± 0.9 nm for the copper oxide NPs and 14.7 ± 0.6 nm for the silver NPs. Surface charge assessment revealed zeta potentials of −21.0 ± 6.5 mV and −24.4 ± 7.9 mV for the copper oxide and silver NPs, respectively. The growth inhibition of C. jejuni by the NPs occurred through attachment to the outer cell membrane and subsequent intracellular internalization and resulted in minimum inhibitory concentrations of the silver NPs at 6 µg/mL and copper oxide NPs at 10 µg/mL. On the other hand, a differential ROS production caused by silver and copper NPs was observed. In summary, this research presents the first demonstration of using green synthesis with the medicinal fungus G. sessile to produce metallic NPs that effectively inhibit C. jejuni growth, providing a sustainable and effective approach to the traditional use of antimicrobials.